2015
DOI: 10.1017/s0022029915000199
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of bap-positiveStaphylococcus aureusstrains from dairy cow mastitis

Abstract: The biofilm-associated protein (Bap) of Staphylococcus aureus is a high molecular weight cell-wall-anchored protein involved in biofilm formation, first described in bovine mastitis strains from Spain. So far, studies regarding Bap were mainly based on the Spanish strain V329 and its mutants, but no information on the genetic variability of bap-positive Staph. aureus strains is yet available in the literature. The present study investigated the molecular characteristics of 8 bap-positive Staph. aureus strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…This represents a cow-associated lineage that has been found in the Americas and in Southern Europe (see MLST database) [22], while studies from Central and Northern Europe failed to detect it [20,21,22,23]. Isolates of this lineage were observed in LP, but also in MHP and HP herds.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This represents a cow-associated lineage that has been found in the Americas and in Southern Europe (see MLST database) [22], while studies from Central and Northern Europe failed to detect it [20,21,22,23]. Isolates of this lineage were observed in LP, but also in MHP and HP herds.…”
Section: Discussionmentioning
confidence: 96%
“…Sed , ser , and sej belong to a cluster harbored by different CCs, out of them CC151 and CC479 were indicated as the most frequent ones [11]. The genes sea , sak and scn , which are carried by β-hemolysin-converting bacteriophages, were present uniquely in some CC8 strains; their prevalence was higher than in other studies on bovine isolates, although lower than in studies on isolates from humans [20,21,22,23,24,25,26,27]. Accordingly, a recent paper reported that CC8 strains of bovine or human origin differed for the mobile genetic elements, among them the β-hemolysin-converting prophages: all bovine-only isolates were devoid of such prophages [28], probably because the untruncated hlb is necessary in ungulates for the different structure of erythrocyte membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Among various surface proteins, biofilm-associated-protein (Bap) was first reported as a large, multi-domain, cell surface anchored protein, which plays a crucial role in S. aureus biofilm development, architecture and in the pathogenesis of bovine mastitis [15][16][17][18][19] . A recent study carried out in Brazil showed the presence of bap gene in all the coagulase-negative Staphylococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports on the role of surface proteins in S. aureus biofilm formation and its stability 8 9 . Among various surface proteins, biofilm-associated protein (Bap) was first reported as a large, multi-domain, cell surface-anchored protein, which plays a crucial role in S. aureus biofilm development, architecture and in the pathogenesis of bovine mastitis 10 11 12 13 . A study carried out in Brazil showed the presence of bap gene in all the coagulase-negative Staphylococcus spp.…”
mentioning
confidence: 99%